Cigarette Consumption, Credit Access, and Determinants Household Food Security in Lampung Province - Tetiyeni Dwi Lestari; Toto Gunarto; Dedy Yuliawan (JSEP (Journal of Social and Agricultural Economics), 2023)
The SDGs emphasize the need to end hunger, improve nutrition and achieve food security. Meeting food needs occurs when everyone has physical and economic access to sufficient, safe and nutritious food. Lampung Province is a province that is a production center for rice, cassava, and corn. This shows that there is the ability of Lampung Province to provide food for its inhabitants. However, regional food availability at the macro level does not guarantee household food security at the micro level. This study uses Susenas raw data for Lampung Province in 2022. Food security status is measured based on a combination of the share of food expenditure and the level of energy consumption which adopts the Jonsson and Toole (1991) indicators to see the effect of several household variables. This study uses ordinal logit regression where the categorization of status is divided into four, namely food insecurity, food deprivation, food vulnerable, and food security. As much as 41,54 percent of households are food secure and 9,5 percent are food insecure. Based on ordinal logit regression analysis, the researchers concluded that the variables affecting household food security in Lampung Province were cigarette consumption, access to credit, social assistance, land assets, internet use, place of residence, income, number of household members, whether the household works on agriculture or not, and age head household.